OXIDATION OF ETHYL ACETATE ON Fe-Mn OXIDES FROM NITRATES DEPOSITED BY IMPREGNATION ON MONOLITHS OF AISI 304 STAINLESS STEEL - Durán, Flavia G.; Barbero, Bibiana P.; Cadús, Luis E. (Journal of the Chilean Chemical Society, 2018)
The iron-manganese mixed monolithic catalysts were obtained by impregnation from nitrates as precursors. A monolithic support was studied with and without alumina as surface generator. The characterization consisted in XRD, SEM, Adherence test, SBET and TPR. The monolith was evaluated in the combustion of ethyl acetate. The preparation method was very satisfactory in terms of reproducibility and adherence of the deposited phase. The higher activity of IFeMnx with respect to Al3FeMnx may be attributed for the formation of the solid solution where the Fe is introduced to the bixbyite structure. However, the presence of defective MnOx species in monoliths without alumina which might help to improve their performance is observed.